A Ludicidade no ensino remoto: contribuições ao processo de alfabetização de crianças do 1º ano de uma escola pública do município de Parintins-AM - Lins, Leia Soares (Brasil, 2021)
This study aimed to investigate how playfulness can contribute to the literacy process of children in the 1st year of a public school in remote education. Therefore, the following specific objectives were outlined: 1) to identify the playful activities used in the literacy of 1st grade children in remote education; 2) describe the perception of literacy teachers regarding the work with playfulness in remote education; and 3) analyze how playfulness as a methodological strategy can contribute to the literacy of children in the 1st year of elementary school in remote education. The investigation was a qualitative field research. First, a bibliographical research was carried out, with a view to carrying out a survey of the works that could serve as theoretical assumptions for the composition of this research. As data collection instruments, direct observation and semi-structured interviews were used. The research subjects were two literacy teachers who teach in the 1st year. The results obtained show that the perception of literacy teachers regarding work with playfulness in remote education showed that the perspective of emergent literacy is directly related to playing, since if there is an environment, interactions and situations, children will use the language of reading or writing in playful situations.